Chemical composition and fermentation pattern of forest trees leaves from Al-Jabal Al-Akhdar region, Libya - Milad, I (Al-Mukhtar Journal of Sciences, 2007)
This study was conducted to determine the chemical composition and the pattern of fermentation of some of forest trees leaves native in AI-Jabal AI-Akhdar region, Libya. Samples included were arbutus Arbutus pavarii, Mediterranean mastic tree Pistacia lentiscus, juniper Juniperus phoenicea, carob Ceratonia siliqua, oak Quercus coccifera. Data obtained in the present study revealed that the percentage of crude protein, crude fibre, crude fat, total mineral ranged as follow (6.3 -11.3), (25.0 -37.0), (5.7 -17.0) and (3.1-8.5) respectively. Measurements of in vitro gas production after incubation of the samples anaerobically with sheep rumen liquor for 72 hrs ranged between 137.3 and 170 ml gm dry matter. In vitro gas production was higher with the genus J. phoenicea (P < 0.01) than with any other genera studied. However, there were no significant differences (P > 0.05) between the other genera. Values of estimated metabolizable energy and organic matter digestibility were 5.23, 5.76, 5.33, 5.70 and 5.73 MJ/Kg DM and 35.5, 39.2, 36.2, 38.3 and, 38.7% for A. pavarii , J. phoenicea, P. lentiscus, C. siliqua and Q. coccifera respectively. There were no significant differences (P > 0.05) between these values. Results of this study indicated that forest trees leaves can be incorporated as a local source for ruminant nutrition under extensive conditions. In addition to that, the pattern of fermentation may indicate the presence of antinutritive factors that may considered.